2011
DOI: 10.1016/j.thromres.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Decline in platelet microparticles contributes to reduced hemostatic potential of stored plasma

Abstract: Introduction In an effort to administer life-saving transfusions quickly, some trauma centers maintain thawed plasma (TP). According to AABB, TP is approved for transfusion for up to five days when stored at 1 – 6 °C. However, the alterations in microparticles (MP) contained in the plasma, which are an integral component of plasma’s hemostatic capacity, are not well characterized. We report on MP changes in TP between its initial thaw (FFP-0) and five days (FFP-5) of storage. Materials and Methods FFP units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…The resulting decline in procoagulant activity was 29%, indicating that PMV numbers decrease in vitro and contribute to in vivo coagulation. 10 The same study also demonstrated that removal of PMV by filtration results in reduced thrombin generation, and that restoration of PMV into the infusion increased the ability for coagulation. The cause of PMV decline in vitro is only speculated; Matijevic et al suggests that extacellular phospholipases may degrade the microvesicles to sub-detectable volumes or that microvesicle coupling to other microvesicles or platelets occurs, forming larger aggregates.…”
Section: Clearancementioning
confidence: 84%
See 1 more Smart Citation
“…The resulting decline in procoagulant activity was 29%, indicating that PMV numbers decrease in vitro and contribute to in vivo coagulation. 10 The same study also demonstrated that removal of PMV by filtration results in reduced thrombin generation, and that restoration of PMV into the infusion increased the ability for coagulation. The cause of PMV decline in vitro is only speculated; Matijevic et al suggests that extacellular phospholipases may degrade the microvesicles to sub-detectable volumes or that microvesicle coupling to other microvesicles or platelets occurs, forming larger aggregates.…”
Section: Clearancementioning
confidence: 84%
“…Platelet microvesicles (PMV) are the most abundant in normal plasma. 7,10 PMV have an important role in the initiation and propagation of coagulation, providing a key focus for hematologic research to improve the safety of cardiac surgery. Their discovery occurred when the clotting time of blood was prolonged following high-speed centrifugation during which PMV became separated from platelet-dense serum, suggesting that PMV enhance coagulation.…”
Section: Microvesicle Physiologymentioning
confidence: 99%
“…Under these conditions, obtained TEG tracings represent fibrin clot generated from plasma clotting factors/inhibitors and residual platelets but without red blood cells or leukocytes given that their presence in plasma products is negligible. 4,15 Statistical Analysis For in vitro permeability assays, data were analyzed using one-way analysis of variance for single time point studies and two-way analysis of variance for time course studies. When significant, an appropriate multiple comparison Holm-Sidak method was applied.…”
Section: Hemostatic Potentialmentioning
confidence: 99%
“…In addition, these MVs play a role as membrane surfaces on which components of the coagulation protease cascade can assemble [12][13][14]. In this context, the plasma MV fraction has been implicated in some adverse transfusion-related events [15,16]. For this reason, it is essential to design and establish quality controls for circulating plasma MVs.…”
Section: Introductionmentioning
confidence: 99%